2021
DOI: 10.31640/jvd.1-2.2021(5)
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risks in Modern Antibiotic Therapy

Abstract: Knowledge of the safety profile of antibacterial drugs is important for rational pharmacotherapy with antibiotics. The purpose of this information is to help the doctor, pharmacist and patient to (quickly) "navigate" in the safety of antibiotics to implement one of the basic principles of pharmacotherapy "Do no harm!". The aim of the study. Analysis of possible potential risks in modern antibiotic therapy. Materials and methods. Analysis of data from the scientific literature on the side effects of antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Also, 5-(1H-indol-3-yl)dihydropyridazine-3,4,6(5H)trione (8) was synthesized through reaction of compound 1 diethyloxalate and Na metal in absolute ethanol at reflux for 12h (Scheme 1). While 2-(1Hindol-3-yl)acetyl azide (9) was prepared via reaction of hydrazide 1 in acidic medium with addition of sodium nitrite portion-wise till effervesces (Scheme 1). Their structures were elucidated through elemental and spectroscopic analyses (cf.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, 5-(1H-indol-3-yl)dihydropyridazine-3,4,6(5H)trione (8) was synthesized through reaction of compound 1 diethyloxalate and Na metal in absolute ethanol at reflux for 12h (Scheme 1). While 2-(1Hindol-3-yl)acetyl azide (9) was prepared via reaction of hydrazide 1 in acidic medium with addition of sodium nitrite portion-wise till effervesces (Scheme 1). Their structures were elucidated through elemental and spectroscopic analyses (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, Acetic acid and αmethyl acetic acid derivatives as mentioned in literature possess high potency degree as antiinflammation drugs. [6][7][8][9][10] Literature survey indicated that nitrogen-rich heterocycles such as triazoles, thiadiazoles, and oxadiazoles have attracted attention of many researchers as they have notable biological properties, especially cytotoxic effects. [11][12][13] These molecules of azoles revealed very intensive antmicrobial, antitumor and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%